Efektivitas Bimbingan Kelompok Teknik Sosiodrama untuk Meningkatkan Kepercayaan Diri Siswa - Al Halik; Nurwahyuni Rakasiwi (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2020)
This research aims to determine teh effectiveness of the guidance of the group of sociodrama techniques in increasing students confidence. This is experimental research using Non-Equivalent Control Group. Research population are students of class VIII SMP Negeri 17 Bekasi, sampling is conducted with the technique Purposive Sampling. The instrument used Likert scale models. Data was analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Samples with SPSS. The findings reveal self-confidence is generally in the medium category. The findings of this research group guidance services using sociodrama method effectively for Increasing the Confidence students. Specifically: there was a significant difference in the student confidence of the experiment groups before and after the guidance of the group of Sociodrama techniques. In the confidence control group the students experienced an insignificant improvement after being given a group guidance treatment without the use of Sociodrama techniques. Furthermore, there is a significant difference in the group's confidence enhancement of student experiments with the control group